2020
DOI: 10.1177/0002764220919145
|View full text |Cite
|
Sign up to set email alerts
|

Laptop or Bust: How Lack of Technology Affects Student Achievement

Abstract: Research shows that digital divides and inequalities are related to lower socioeconomic status and detrimental to social and economic capital acquisition. Other studies show that use of information and communication technologies in the classroom can lead to worse academic performance. Nevertheless, many universities require that students own or buy a laptop, and many offer financial aid for students who cannot afford to buy one. As such, laptop ownership may be crucially tied to academic performance. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 37 publications
(55 reference statements)
1
20
0
2
Order By: Relevance
“…To date, cross-sectional studies have associated first or second-level digital inequality to interim outcomes. For example, Reisdorf and colleagues found that students at a large, public U.S. university who did not have a laptop during their freshman year had a lower first-year Grade Point Average (GPA), after controlling for other factors [26]. Gonzales and colleagues made a similar connection between technological maintenance issues and end-ofterm GPAs [9].…”
Section: Digital Inequality and Undergraduates' Online Learning Expermentioning
confidence: 99%
“…To date, cross-sectional studies have associated first or second-level digital inequality to interim outcomes. For example, Reisdorf and colleagues found that students at a large, public U.S. university who did not have a laptop during their freshman year had a lower first-year Grade Point Average (GPA), after controlling for other factors [26]. Gonzales and colleagues made a similar connection between technological maintenance issues and end-ofterm GPAs [9].…”
Section: Digital Inequality and Undergraduates' Online Learning Expermentioning
confidence: 99%
“…Researchers have warned that the closure of schools and guidelines to stay inside the home will have short-and long-term effects on students' physical and socio-emotional well-being, and are likely lead to increases in domestic violence, loneliness, depression, fear, panic, anxiety and substance use among students (Radwan, Radwan and Radwan, 2020 [7]). Furthermore, these effects may be experienced disproportionately among the most vulnerable and marginalised students in local communities and exacerbate existing disparities observed within education systems (UNESCO, 2020 [8]) 3 . Research has also shown that gender bias often leaves parents with limited resources more likely to invest in the education of their male children over their female children, making female students more likely to drop out of school than their male peers (Shahidul, 2015[9]).…”
Section: Educational Disruptions Due To Covid-19mentioning
confidence: 99%
“…This type of in-depth analysis is particularly important to recognize barriers to access and other unequal experiences of emergency e-learning. Pre-pandemic, laptop ownership (Reisdorf, Triwibowo, and Yankelevich 2020) and technology maintenance and dependability (Gonzales, Calarco, and Lynch 2020) already pointed out how socioeconomic barriers lead to an unequal experience of postsecondary education. In the age of emergency e-learning, when laptops and dependable connections are not only necessary for assignments and reading but also for the course experience, the socioeconomic barrier increases.…”
mentioning
confidence: 99%